Spermidine metabolism in parasitic protozoa--a comparison to the situation in prokaryotes, viruses, plants and fungi - Kaiser, Annette E; Gottwald, Andrea M; Wiersch, Carolin S; Maier, Walter A; Seitz, Hanns M (Folia parasitologica, 2003)
Targeting polyamines of parasitic protozoa in chemotherapy has attracted attention because polyamines might reveal novel drug targets for antiparasite therapies (Müller et al. 2001). The biological function of the triamine spermidine in parasitic protozoa has not been studied in great detail although the results obtained mainly imply three different functions, i.e., cell proliferation, cell differentiation, and biosynthesis of macromolecules. Sequence information from the malaria genome project databases and inhibitor studies provide evidence that the current status of spermidine research has to be extended since enzymes of spermidine metabolism are present in the parasite (Kaiser et al. 2001). Isolation and characterisation of these enzymes, i.e., deoxyhypusine synthase (EC 1.1.1.249) (DHS) and homospermidine synthase (EC 2.5.1.44) (HSS) might lead to valuable new targets in drug therapy. Currently research on spermidine metabolism is based on the deposition of the deoxyhypusine synthase nucleic acid sequence in GenBank while the activity of homospermidine synthase was deduced from inhibitor studies. Spermidine biosynthesis is catalyzed by spermidine synthase (EC 2.5.1.16) which transfers an aminopropyl moiety from decarboxylated S-adenosylmethionine to putrescine. Spermidine is also an important precursor in the biosynthesis of the unusual amino acid hypusine (Wolff et al. 1995) and the uncommon triamine homospermidine in eukaryotes, in particular in pyrrolizidine alkaloid-producing plants (Ober and Hartmann 2000). Hypusine is formed by a two-step enzymatic mechanism starting with the transfer of an aminobutyl moiety from spermidine to the epsilon-amino group of one of the lysine residues in the precursor protein of eukaryotic initiation factor eIF5A by DHS (Lee and Park 2000). The second step of hypusinylation is completed by deoxyhypusine hydroxylase (EC 1.14.9929) (Abbruzzese et al. 1985). Homospermidine formation in eukaryotes parallels deoxyhypusine formation in the way that in an NAD(+)-dependent reaction an aminobutyl moiety is transferred from spermidine. In the case of homospermidine synthase, however the acceptor is putrescine. Thus the triamine homospermidine consists of two symmetric aminobutyl moieties while there is one aminobutyl and one aminopropyl moiety present in spermidine. Here, we review the metabolism of the triamine spermidine with particular focus on the biosynthesis of hypusine and homospermidine in parasitic protozoa, i.e., Plasmodium, Trypanosoma and Leishmania, compared to that in prokaryotes i.e., Escherichia coli, a phytopathogenic virus and pyrrolizidine alkaloid-producing plants (Asteraceae) and fungi.
Keywords: zvířata; spermidin; Animals; Eukaryota; Leishmania; Plasmodium falciparum; Spermidine; Trypanosoma